1991
DOI: 10.1002/ijc.2910490619
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐cell killing by MAbs against fucosyl GM1, a ganglioside antigen associated with small‐cell lung carcinoma

Abstract: Monoclonal antibodies (MAbs) reactive with the ganglioside fucosyl GM1 (Fuc-GM1), an antigen associated with small-cell carcinoma of the lung (SCLC), were tested for their ability to mediate tumor-cell killing in vitro in conjunction with humoral and cellular effectors and to inhibit tumor engraftment in nude mice in vivo. MAbs F12 and F15, both IgG3k, induced human complement-mediated cytolysis of 3 Fuc-GM1-expressing tumor cell lines: one rat hepatoma cell line, H4-II-E, and 2 human SCLC cell lines, NC1 H69 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The fact that it is an exclusively antigen expressed on SCLC cells turns it into an appropriate candidate for therapy. Related to this, two monoclonal antibodies against fucosyl-GM1 (F12 and 15) induced CDC and ADCC in fucosyl-GM1 expressing cell lines in vitro , and also conferred protection against tumor engraftment in a mouse model (103). In clinical trials of immunization with fucosyl-GM1-KLH conjugate, SCLC patients demonstrated serological IgM and IgG responses against fucosyl-GM1 and in vitro CDC of fucosyl-GM1 positive cell lines (104).…”
Section: Immunotherapies Using Ganglioside Fucosyl-gm1 As the Targetmentioning
confidence: 94%
“…The fact that it is an exclusively antigen expressed on SCLC cells turns it into an appropriate candidate for therapy. Related to this, two monoclonal antibodies against fucosyl-GM1 (F12 and 15) induced CDC and ADCC in fucosyl-GM1 expressing cell lines in vitro , and also conferred protection against tumor engraftment in a mouse model (103). In clinical trials of immunization with fucosyl-GM1-KLH conjugate, SCLC patients demonstrated serological IgM and IgG responses against fucosyl-GM1 and in vitro CDC of fucosyl-GM1 positive cell lines (104).…”
Section: Immunotherapies Using Ganglioside Fucosyl-gm1 As the Targetmentioning
confidence: 94%
“…Since fucosyl GM1 is abundantly present on SCLC cells in clinical tumor specimens, SCLC cells would have been a more relevant target in this study. However, the expression of fucosyl GM1 on SCLC cells cultured in vitro is very heterogeneous on the cell lines hitherto available [18,20]. Work is in progress to identify SCLC cell lines that have homogeneous expression of fucosyl GM1 to be used for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that MAbs are able to activate complement in vitro resulting in the death of tumor cell targets [20,26,27]. The mechanisms that lead to cell death are thought to be mediated by the formation of complexes of the late complement factors, C5b-C9 (membrane attack complex) [28] which are inserted into the cell membrane resulting in a disturbance of intracellular homeostasis finally leading to cell lysis and death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was not until recently that cytotoxic activity was achieved in vivo with mAb against known cluster antigens (cluster w4 and 5A) (95). Brezicka et al demonstrated ADCC against FucGM,-positive cells both in vitro and in vivo (18). The ganglioside FucGMl is found in few normal tissues except the small intestine and pancreas (78).…”
Section: Carbohydrate Antigens As Therapeutic Targetsmentioning
confidence: 99%